Experience in the diagnosis and treatment of Kawasaki disease in the Saint-Petersburg State Pediatric Medical University Clinic and Saint Petersburg City Children’s Hospital One - A. V. Santimov; R. A. Rupp; I. G. Alekseev; N. N. Plutova; E. A. Moskvina; M. K. Kruchina; A. N. Tarasenko; N. E. Sokolova; E. A. Savelyeva; I. Yu. Bogdanov; D. V. Ivanov; T. I. Kandrina; et al. (Современная ревматология, 2017)
Kawasaki disease (KD) is acute systemic vasculitis of unknown etiology. Approximately 20–25% of untreated patients develop coronary artery changes with a range of severity from asymptomatic coronary artery dilatation to giant coronary artery aneurysms with thrombosis, myocardial infarction, and sudden death. To date there is no official data on the incidence of KD in Russia. In Russia, the disease is not enough known now to a wide circle of physicians and often masks other more common diseases. Since 2010, the detection rate of KD has dramatically increased in Saint-Petersburg.Objective: to analyze the experience in diagnosing and treating KD in two largest hospitals of Saint Petersburg.Patients and methods. The retrospective study included data on 30 children (18 boys, 12 girls) who were hospitalized with a diagnosis of KD in the Saint-Petersburg State Pediatric Medical University Clinic and Children’s Hospital One (Saint Petersburg) between January 2011 and September 2016. Data are represented by median and extreme values. The age of the children was 2.8 (0.2; 4.6) years; of them 5 (16.7%) patients were under the age of 1 year. The children were hospitalized on 5 (1; 14) days of disease onset; KD was diagnosed on 9 (3; 52) day of the disease.Results. Immediately after diagnosis, 27 (90%) children received aspirin. In early stages (before 10 days of the disease), intravenous immunoglobulin (IVIG) therapy was performed in 15 (50%) children, one of them received IVIG before disease day 5 (on day 3), but without effect. On disease days 11-20 (immediately after diagnosis), 10 (33.3%) children were prescribed with IVIG; thereafter fever was abolished in all the patients. Their body temperature became normal on day 11 (6; 23). Ultrasonography revealed coronary artery lesions in 13 (43.3%) patients. Out of the 30 children followed up, one baby who fell ill at the age of 3 months and received IVIG died on day 30 of the disease.Conclusion. Currently, there continues to be a delayed diagnosis of KD. IVIG therapy was effective, especially in cases of timely diagnosis. It is necessary to increase awareness of KD among clinicians and ultrasound diagnosticians.